OIL AND RUSSIA’S POLITICAL REGIME AT STAGES IN POST-COMMUNIST DEVELOPMENT: CONTINUITY OF RENT SEEKING WITHIN THE RAW-MATERIAL PARADIGM - MAGOMEDOV, Arbakhan (CENTRAL ASIA AND THE CAUCASUS, 2010)
On 28 April 2010, during a business trip to Astrakhan on the Caspian, Russian Prime Minister Vladimir Putin personally pushed the button to start the region’s first drilling unit on the Korchagin platform. This moved Russia offshore in its sector of the Caspian and confirmed that the Kremlin was as determined as ever to remain within the raw-material paradigm; the nature of the political stimuli in the corridors of power became much clearer.It should be said that the rent-seeking angle throws the most typical features of Russia’s political regime into bolder relief.Here I have examined the rent-seeking phenomenon of Russian power at various stages of post-communist development in the oil sphere, the country’s key resource, and the correlation between the raw-material opportunities and the principles of political organization in Putin’s Russia.